Analysis of Traffic Violations and Accidents with Enforcement: A Study in Jimma Town - Tarekegn Reta Mesfin; Eba Kitata Kenea (Three E Science Institute, 2022)
The level of enforcement of road traffic laws plays a significant role in reducing traffic accidents, especially pedestrians, who are more than a fifth of the 1.24 million people killed each year due to traffic accidents. For assessing traffic law enforcement, the registered traffic violation data for the years 2015-2017 were taken from the Traffic Police Department to describe the activities of traffic police personnel in enforcing traffic laws. The violations were categorized into four groups: -those related to driving, vehicle, parking, and others, and Traffic Law Enforcement into safety and other traffic law enforcement activities. The vehicles involved in the violations were categorized as cars, small load vehicles, motorcycles, Bajaj, etc. Traffic Police had registered 77 traffic law violations in the year 2015, 65 in the year 2016, and 86 in the year 2017. Driving violation was the highest registered violation in the three years, and it was slightly higher in 2017. The cars and small load vehicles categories were the highest registered vehicles in several violations within the three years. For motorized two-wheeled vehicles, the highest number of registered violations in the three years was the one related to driving. All vehicle-related and other violations were registered more commonly for cars in 2015 and 2016. Of the registered violations, the parking-related violation occurred only in 2017. Safety-related traffic law enforcement was 89.96% of the total traffic law enforcement activity.